Edukasi dan Sosialisasi Pencegahan dan Pengendalian COVID-19 melalui Media Poster di Desa Bojongsoang, Kabupaten Bandung - Caesaron, Dino; Salma, Sheila Amalia; Prasetio, Murman Dwi; Rifai, Mohammad Husain (University of Merdeka Malang, 2021)
The COVID-19 virus has infected many people, resulting in death tolls around the world. So, it is necessary to adopt a clean and healthy lifestyle and implement health protocols such as using masks, washing hands and maintaining distance. This community service activity aims to provide education and assistance to community representatives in Desa Bojongsoang, Bandung, to always implement a healthy and clean lifestyle and health protocols. Educational activities are carried out by providing counseling with the methods of lectures, discussions, and questions and answers. Material delivery is also conveyed through the media of posters, so that the posters can be affixed to strategic areas so that it can be seen and read effectively. In this activity, an evaluation of the level of community compliance in implementing health protocols while outside the home was also carried out, by distributing questionnaires before the activity took place. As a result, in general the community is disciplined in applying health protocols while outside the home. Several findings were also obtained in this simple survey, so that these findings can be used as initial data/information for local stakeholders to streamline education and socialization in efforts to prevent the massif transmission of the COVID-19 virus.DOI:Â https://doi.org/10.26905/abdimas.v6i2.5354